This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: \ Fx = 0 And, ∂σ y + ∂τ xy + ∂τ yz + Fy = 0 ∂ y ∂ x ∂ z ∂ (2.y 2 ) + ∂ (z +4.x.y 7 )+ ∂ ( 0 )+ Fy = 0 ∂ y ∂ x ∂ z 4.y + 4.y +0 +Fy = 0 \ Fy = 0 ∂σ z + ∂τ zx + ∂τ zy + Fz = 0 ∂ z ∂ x ∂ y ∂ ( 3.x +y+ 3.z5 ) + ∂ ( 3.x +y+1 ) + ∂ ( 0) + Fz = 0 ∂ z ∂ x ∂ y 33+0+Fz = 0 \ Fz = 0 Final Answer: = = = F F F Z Y X...
View
Full
Document
This note was uploaded on 11/22/2011 for the course EML 6653 taught by Professor Law during the Fall '09 term at University of South Florida  Tampa.
 Fall '09
 Law
 Stress

Click to edit the document details